Myocardial Dysfunction in Acute Traumatic Brain Injury Relieved by Surgical Decompression - Vijay Krishnamoorthy; Deepak Sharma; Sumidtra Prathep; Monica S. Vavilala (Case Reports in Anesthesiology)
Traumatic brain injury (TBI) is a major public health issue and is a leading cause of death in North America. After a primary TBI, secondary brain insults can predispose patients to a worse outcome. One of the earliest secondary insults encountered during the perioperative period is hypotension, which has been directly linked to both mortality and poor disposition after TBI. Despite this, it has been shown that hypotension commonly occurs during surgery for TBI. We present a case of intraoperative hypotension during surgery for TBI, where the use of transthoracic echocardiography had significant diagnostic and therapeutic implications for the management of our patient. We then discuss the issue of cardiac dysfunction after brain injury and the implications that echocardiography may have in the management of this vulnerable patient population.